Effect of L/D Ratio and the Temperature on MR Fluid Squeeze Film Damper Performance - Saravanakumar, G.; Ravikumar, L. (Asian Journal of Engineering and Applied Technology, 2014)
Magnetorheological fluid squeeze film dampers are latest devices used to ease out small amplitude, large force vibrations in high speed aircraft jet engines to provide external damping. Magnetorheological fluids are controllable fluids wherein the rheological properties of the fluid like viscosity can be controlled by varying the magnetic field intensity to meet the demands of the rotor dynamic system. Magnetorheological fluids can be utilized in squeeze film dampers, to provide variable stiffness and damping at a particular excitation frequency by controlling the current through the coils of the magnet. A study is carried out to establish the dynamic characteristics of these fluids as a function of temperature. The temperature is raised by 10oC as given in the literature and variation in viscosity and its effect on dynamic characteristics is evaluated theoretically. These characteristics are found to be decreasing with increase in temperature. The dynamic characteristics are evaluated and their effects are studied very clearly for every 10oC rise in temperature. The aim of the research is to provide information of the temperature effect and the L/D ratio on Magnetorheological fluid squeeze film dampers as the aircraft jet engine rotors are located in a zone of high temperature gradients in addition to the heat generated due to the current in the magnetic coils and the damper fluid is sensitive to large variations in temperature.